Extraction of hydrocarbons from freshwater green microalgae (Botryococcus sp.) biomass after phycoremediation of domestic wastewater - Gani, Paran; Mohamed Sunar, Norshuhaila; Matias- Peralta, Hazel Monica; Radin Mohamed, Radin Maya Saphira; Abdul Latiff, Ab Aziz; Parjo, Umi Kalthsom (Taylor & Francis, 2017)
This study was undertaken to analyze the efﬁciency of Botryococcus sp. in the phycoremediation of domestic wastewater and to determine the variety of hydrocarbons derived from microalgal oil after phycoremediation. The study showed a signiﬁcant (p < 0.05) reduction of pollutant loads of up to 93.9% chemical oxygen demand, 69.1% biochemical oxygen demand, 59.9% total nitrogen, 54.5% total organic carbon, and 36.8%phosphate. The average dry weight biomass produce was 0.1 g/L of wastewater. In addition, the dry weight biomass of Botryococcus sp. was found to contain 72.5% of crude oil. The composition analysis using Gas Chromatogram - Mass Spectrometry (GC-MS) found that phthalic acid, 2-ethylhexyltridecyl ester (C29H48O4), contributed the highest percentage (71.6%) of the total hydrocarbon compounds to the extracted algae oil. The result of the study suggests that Botryococcus sp. can be used for effective phycoremediation, as well as to provide a sustainable hydrocarbon source as a value-added chemical for the bio-based plastic industry.